2009
DOI: 10.1262/jrd.20208
|View full text |Cite
|
Sign up to set email alerts
|

Immunodetection of NGF, trkA, p75 and Inhibin .ALPHA.-Subunit in Interstitial Cells of Golden Hamsters Treated with hCG

Abstract: Abstract. The aim of this study was to investigate the effect of luteinizing hormone (LH) surge on expression of nerve growth factor (NGF), trkA, p75 and inhibin α-subunit in ovarian interstitial cells of golden hamsters after human chorionic gonadotropin (hCG) treatment. NGF, two NGF receptors (trkA, p75) and inhibin α-subunit were immunolocalized by immunohistochemistry, and gonadotropins, steroid hormones and immunoreactive (ir-) inhibin concentrations were measured by radioimmunoassay. Stronger positive st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 54 publications
(80 reference statements)
1
16
0
Order By: Relevance
“…The notion that gonadotrophins influence the expression of neurotrophins is also supported by the finding that NGF follicular fluid concentrations increased dramatically in ovine large, antral follicles in response to gonadotrophin stimulation (Barboni et al 2002) and in golden hamsters, the LH surge induced NGF, NTRK1 and NGFR protein expression in ovarian interstitial cells (Weng et al 2009). Furthermore, BDNF secretion by cumulus and granulosa cells was increased in women undergoing IVF in response to treatment with LH, human chorionic gonadotrophin (hCG) or menopausal urinary gonadotrophin (Feng et al 2003), and a recent study conducted by Zhao et al (2011) demonstrated that both GDNF and BDNF mRNA levels were slightly increased following FSH treatment of unstimulated human granulosa cells derived from women undergoing IVM (Zhao et al 2011).…”
Section: R49mentioning
confidence: 90%
“…The notion that gonadotrophins influence the expression of neurotrophins is also supported by the finding that NGF follicular fluid concentrations increased dramatically in ovine large, antral follicles in response to gonadotrophin stimulation (Barboni et al 2002) and in golden hamsters, the LH surge induced NGF, NTRK1 and NGFR protein expression in ovarian interstitial cells (Weng et al 2009). Furthermore, BDNF secretion by cumulus and granulosa cells was increased in women undergoing IVF in response to treatment with LH, human chorionic gonadotrophin (hCG) or menopausal urinary gonadotrophin (Feng et al 2003), and a recent study conducted by Zhao et al (2011) demonstrated that both GDNF and BDNF mRNA levels were slightly increased following FSH treatment of unstimulated human granulosa cells derived from women undergoing IVM (Zhao et al 2011).…”
Section: R49mentioning
confidence: 90%
“…These results were similar to those found in golden hamsters and pigs. Previous studies in golden hamster have suggested that LH surge may be an important factor for inducing the expression of NGF, TrkA, p75 in ovarian tissues periodically [16,18]. In pig ovary, the increase in expression of NGF and TrkA in large follicles found on day 20 may also result from an LH effect [35].…”
Section: Discussionmentioning
confidence: 99%
“…These results implied that NGF may act indirectly in follicular development through the production of biologically active FSHR [13]. In golden hamsters, as one member of TGFβ superfamily, inhibin α-subunit might works in concert with NGF and its receptors to act on LH/hCG receptor expression in ovarian interstitial cells and associated with the ovulatory process [18]. Also, our previous studies showed that inhibin/activin subunits (α, β(A) and β(B)) were present in granulosa cells, theca cells of antral follicles and interstitial cells in the breeding season ovary of wild ground squirrel, following ovulation, the corpora lutea become a major site of inhibin/activin synthesis [29].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 4-6 In recent years, the studies of NGF and its receptors in reproductive system largely focus on the immunolocalization and expression of NGF system in reproductive organs, 7 , 8 the functional role of NGF system in the follicular development 9 , 10 and in spermatogenesis. 11-12 The studied species range from experimental models, such as rat, 7 , 8 , 11 mouse 12 and golden hamster, 13 , 14 to primate 15 and human. 16 , 17 Our previous results indicated that NGF and its receptors may be involved in the regulation of seasonal changes in the ovarian and uterine functions of wild female ground squirrels.…”
Section: Introductionmentioning
confidence: 99%